1996
DOI: 10.1034/j.1600-0870.1996.00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Polar lows in the Labrador Sea. A case study

Abstract: In this paper, we will describe our analysis of a polar low event that occurred in the Labrador Sea during the winter of 1992. As there are unfortunately no in‐situ observations of this event, we will rely on satellite data as well as the high‐resolution objective analaysis from the ECMWF to document the environment in which the low developed and the structure of the low itself. We will show that the polar low developed during a cold air outbreak that was precipitated by the passage of an intense synoptic‐scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…With the advent of satellite imagery it has become apparent that polar mesocyclones are frequent in both hemispheres of the subarctic Atlantic and Pacific Oceans (see, e.g., Businger 1987;Carleton and Carpenter 1990;Harold et al 1999a). In the North Atlantic, vortices are commonly observed over both the Labrador Sea (Moore et al 1996;Rasmussen et al 1996) and the Greenland Sea (Harold et al 1999a;Shapiro et al 1987;Nordeng and Rasmussen 1992) in regions where intense buoyancy loss due to heat exchange with the overlying atmosphere and sea ice formation are important for initiating localized violent open-ocean convection that mixes the surface waters to great depths, given suitable preconditioning (Marshall and Schott 1999;Wadhams et al 2002). The water mass modifications that occur in these regions due to convection appear to be the main Northern Hemisphere control on the strength of the thermohaline circulation, and thus have far-reaching effects on the climate system (Marshall and Schott 1999).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of satellite imagery it has become apparent that polar mesocyclones are frequent in both hemispheres of the subarctic Atlantic and Pacific Oceans (see, e.g., Businger 1987;Carleton and Carpenter 1990;Harold et al 1999a). In the North Atlantic, vortices are commonly observed over both the Labrador Sea (Moore et al 1996;Rasmussen et al 1996) and the Greenland Sea (Harold et al 1999a;Shapiro et al 1987;Nordeng and Rasmussen 1992) in regions where intense buoyancy loss due to heat exchange with the overlying atmosphere and sea ice formation are important for initiating localized violent open-ocean convection that mixes the surface waters to great depths, given suitable preconditioning (Marshall and Schott 1999;Wadhams et al 2002). The water mass modifications that occur in these regions due to convection appear to be the main Northern Hemisphere control on the strength of the thermohaline circulation, and thus have far-reaching effects on the climate system (Marshall and Schott 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Many other studies have also found that UPV anomalies are an integral factor in PL developments (e.g. Montgomery and Farrell, 1992;Mailhot et al, 1996;Moore et al, 1996;Bresch et al, 1997;Browning and Dicks, 2001;Moore and Vachon, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…While in its early years polar low research was mainly focused on the areas of European polar seas, polar MCs are now investigated over almost all oceans affected by cold air outbreaks in the Northern Hemisphere (NH) and also in the Southern Hemisphere (SH). For the NH, research has been conducted, for example, for the Japan Sea (Ninomiya 1991;Matsumoto et al 1982); the Bering Sea, the Gulf of Alaska, and the North Pacific (Businger and Baik 1991;Businger 1987;Reed 1979); the Labrador Sea, Hudson Bay, and the Davis Strait (Roch et al 1991;Rasmussen et al 1996;Moore et al 1996); and also for the areas of the Greenland Sea, the Norwegian Sea, and the Barents Sea (e.g., Lystad 1986;Businger 1985;Rasmussen 1985).…”
Section: Introductionmentioning
confidence: 99%